Rural Families' Process of Re‐Forming Environmental Health Risk Messages. Issue 4 (15th June 2015) - Oneal, Gail A.; Eide, Phyllis; Hamilton, Rebekah; Butterfield, Patricia; Vandermause, Roxanne
Abstract Purpose This study was undertaken to explore how rural low‐income families with children process health information following a nurse‐delivered intervention designed to reduce environmental risks in their homes. Design and Method Grounded theory methodology with a constructivist approach was used to conduct the study. Semistructured interviews of 10 primary child caregivers in rural low‐income families who had participated in an environmental risk reduction intervention were completed from 2009 to 2011. Data were categorized using comparative analysis, theoretical sampling, and coding techniques. Findings The three phases—(a) visiting my perception, (b) weighing the evidence, and (c) making a new meaning—explained the core process of the grounded theory of Re‐Forming the Risk Message. Conclusions Rural low‐income families at risk for environmental hazards in their homes determined what health information and needed subsequent actions regarding their risks were important by changing the meanings of nurse‐delivered messages. Clinical Relevance Nursing interventions designed to improve health behaviors and reduce risks are often based on stage theories that explain how change occurs through steps leading to positive actions through delivery of risk messages. However, the risk message delivered in an intervention designed to engage action is not always the risk message people decide to use. To understand whether people are ready to engage in positive behaviors through interventions, or if needed changes to the information must be made, nurses need to discover and explore reasons for the re‐formed risk messages.